Über das Leben Raffaels von Urbino - Die Göttinger Vorlesung aus dem Jahr 1841 - Oesterley, Carl; Mikolajczak, Katja; Thimann, Michael; Reiss, Steven (2019)
Computer Systems Organization and Communication Networks; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics); Simulation and Modeling; anomaly detection, anti-fragility, cloud computing, complex adaptive systems, DevOps (Development and Operation), diversity, loose coupling